The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Current Challenges in Childbirth 2023
DOI: 10.5772/intechopen.104445
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labour

Abstract: Induction of labour is one of the common obstetric interventions in the world with varied incidence rates between developed and developing countries. It is generally employed by obstetricians and physicians managing pregnant women when the risk of continuing such pregnancy is far greater than delivery at that said point. A detailed evaluation and indications for induction of labour should be done for every single woman. Methods of induction of labour could be pharmacological, mechanical or both; taking care to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Compared with the WHO Global Survey of 20 Indian healthcare facilities in 2007-2008, 4 the present findings suggest a potential threefold increase in the prevalence of labour induction in India (from 12.8% in the WHO survey to 42.3% in our study) over two decades, with induction using pharmacological agents alone being the predominant method (77.4% in the WHO survey vs. 58.8% in our study). Also, the WHO Global Survey 4 and our study consistently found that fetal-related complications and hypertensive disorders in pregnancy were the most common indications for induction (representing at least 10% of inductions), and identified similar proportions of induction of labour without any clinical indication as per guidelines 810 23–25 (32.1% in WHO survey vs. ∼31% in our study). The increased utilization of induction of labour may be partially explained by improved diagnosis or increasing prevalence of maternal and/or fetal complications, but this also depends on what is reported in the labour management records.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Compared with the WHO Global Survey of 20 Indian healthcare facilities in 2007-2008, 4 the present findings suggest a potential threefold increase in the prevalence of labour induction in India (from 12.8% in the WHO survey to 42.3% in our study) over two decades, with induction using pharmacological agents alone being the predominant method (77.4% in the WHO survey vs. 58.8% in our study). Also, the WHO Global Survey 4 and our study consistently found that fetal-related complications and hypertensive disorders in pregnancy were the most common indications for induction (representing at least 10% of inductions), and identified similar proportions of induction of labour without any clinical indication as per guidelines 810 23–25 (32.1% in WHO survey vs. ∼31% in our study). The increased utilization of induction of labour may be partially explained by improved diagnosis or increasing prevalence of maternal and/or fetal complications, but this also depends on what is reported in the labour management records.…”
Section: Discussionsupporting
confidence: 80%
“…Approximately two-thirds of the methods used for labour induction or augmentation were pharmacological only. Consistent with current guidelines for labour induction, 810 23–25 the greater the number of maternal and fetal clinical indications a woman had, the more likely her labour was to be induced, whereas women with any contraindication were less likely to be induced. Similarly, women with fewer clinical indications or contraindications for induction were less likely to undergo labour augmentation.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations